Preparation method of water purification filler with adsorption and photo-Fenton properties
Through hydrothermal synthesis of FeOOH/aMIL-125 composite catalyst, combined with photocatalytic technology and Fenton reaction, the problem of photogenerating electrons and holes of FeOOH was solved, and the rapid circulation of Fe(III)/Fe(II) and the improvement of pollutant degradation efficiency was achieved.
Patent Information
- Application Number
- CN202510093943.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-21
AI Technical Summary
FeOOH photogenerated electrons and holes are prone to recombination, resulting in slow conversion of Fe(III)/Fe(II) and affecting the efficiency of pollutant degradation.
The FeOOH/aMIL-125 composite catalyst is synthesized by hydrothermal, combined with photocatalytic technology and Fenton reaction, promote the separation of electrons and holes and the circulation of Fe(III)/Fe(II), and realize the self-cleaning function.
It improves the practical application value of FeOOH/aMIL-125 water purification filler and enhances the degradation efficiency of organic pollutants such as antibiotics.
Smart Images

Figure CN119869619A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of water purification fillers, and in particular relates to a method for preparing a water purification filler with adsorption and photo-Fenton properties. Background Art
[0002] In recent years, up to 60% of natural rivers have been contaminated by antibiotics. Tetracycline hydrochloride (TC-HCl) is a cheap and readily available antibiotic that has been widely used in healthcare, animal husbandry, and aquaculture. Due to its widespread use, TC-HCl inevitably infiltrates into natural ecosystems, which has prompted extensive research on environmental solutions. The photo-Fenton reaction is an advanced oxidation technology that eliminates organic pollutants such as antibiotics by decomposing hydrogen peroxide (H2O2) to produce hydroxyl radicals (·OH). This process is driven by photoelectrons and establishes a Fe(III) / Fe(II) cycle under the promotion of photocatalysts.
[0003] FeOOH is a narrow-bandgap semiconductor that exhibits good visible light response and stability in heterogeneous photocatalysis and is widely used in photo-Fenton reactions due to its low cost, non-toxicity and wide pH range. However, the photogenerated electrons and holes in FeOOH are prone to recombination, resulting in slow Fe(III) / Fe(II) conversion, which affects the pollutant degradation efficiency in practical applications.
[0004] In the past few decades, metal organic frameworks (MOFs) have developed into the next generation of excellent solid porous crystalline materials. MIL-125 (Ti) is a Ti-MOF that has been widely used in many fields such as adsorption, photocatalysis, electrode materials and virus therapy. It has ultra-high specific surface area, large porosity, adjustable structure, variable functionality and multiple active sites for photocatalytic reactions. Under light, this process can proceed spontaneously, so it is a new generation of catalytic materials with self-cleaning function. Summary of the invention
[0005] The present invention aims at the above problems and provides a method for preparing a water purification filler with adsorption and photo-Fenton properties.
[0006] To achieve the above object, the present invention adopts the following technical solution, which includes the following steps: Step 1) dissolving FeCl3·6H2O in deionized water, stirring to obtain a uniform orange solution, and then placing the solution in a reactor for hydrothermal treatment; after the reactor is naturally cooled to room temperature, washing the obtained product with ethanol and deionized water to obtain a solid product; Step 2) The product obtained in step 1) is placed in an oven and dried to obtain a dark red powder substance FeOOH; the obtained FeOOH and L-cysteine are dissolved in deionized water, stirred, collected and washed with ethanol; after drying in an oven, a wine red powder substance L-FeOOH is obtained; Step 3) mixing the obtained L-FeOOH with N,N-dimethylformamide (DMF) and methanol by ultrasonication to obtain a uniform solution; Step 4) adding terephthalic acid to the solution obtained in step 3), stirring evenly and then adding tetrabutyl titanate dropwise; Step 5) The solution obtained in step 4) is placed in a reaction kettle and hydroheated; the solid matter after hydroheating is then washed with ethanol and dried in an oven to finally obtain a wine red powder substance FeOOH / aMIL-125-0.3.
[0007] As a preferred embodiment, in step 1) of the present invention, the mass ratio of FeCl3·6H2O to deionized water is 3:200.
[0008] As another preferred embodiment, in step 1) of the present invention, the ratio of the volume of deionized water to the volume of the reactor is 2:5; this can better ensure that the pressure in the hydrothermal reaction process promotes the synthesis of substances.
[0009] As another preferred embodiment, in the step 1 of the present invention, 0.5-0.6 g of FeCl3·6H2O is dissolved in 30-50 mL of deionized water, and stirred for 10-15 minutes using a multi-head magnetic stirrer at a frequency of 30-35 Hz (preferably 33.33 Hz). After obtaining a uniform orange solution, the solution is placed in a 90-120 mL reactor and hydrothermal at 150-200° C. for 700-750 min; after the reactor is naturally cooled to room temperature, the obtained product is centrifuged with ethanol and deionized water at a speed of 8000-9000 rpm for 3-5 minutes to obtain a solid product. Setting the frequency and stirring time of the magnetic stirrer can limit the degree of mixing and control the particle size of the catalyst. The magnetic stirrer can be a HJ-4 type magnetic stirrer. Centrifugal washing helps to clean the material and separate the solid and liquid, and a 220V 60Hz centrifuge (TG16) can be used for centrifugal washing.
[0010] As another preferred embodiment, in step 2) of the present invention, the mass ratio of FeOOH, L-cysteine and deionized water is 1:1:12.
[0011] When the ratio of FeOO to L-cysteine is 1:1, the composite synthesis can be better carried out, while the ratio of solid material to deionized water is 1:12, which is conducive to the uniform dissolution of the solid.
[0012] As another preferred embodiment, in the step 2) of the present invention, the product obtained in step 1) is placed in an oven at 60-80° C. and dried for 9-12 hours to obtain a dark red powder substance FeOOH; 0.3-0.5 g of FeOOH and 0.3-0.5 g of L-cysteine are dissolved in 30-40 mL of deionized water, stirred for 20-30 hours, collected and washed with ethanol; after drying in an oven at 60-80° C. for 9-12 hours, a wine red powder substance L-FeOOH is obtained.
[0013] As another preferred embodiment, in step 3) of the present invention, the mass ratio of L-FeOOH, N,N-dimethylformamide and methanol is 1:120:14.
[0014] This ratio helps N,N-dimethylformamide and methanol to be miscible and react well with L-FeOOH.
[0015] As another preferred embodiment, in step 3) of the present invention, 0.1-0.6 g of L-FeOOH obtained is mixed with 35-40 mL of N,N-dimethylformamide and 3-5 mL of methanol by ultrasonic cleaning (Kunshan Shumei KQ2200 ultrasonic cleaning machine can be used) at a frequency of 80-100 Hz for 10-15 minutes to obtain a uniform solution.
[0016] As another preferred embodiment, in step 4) of the present invention, the mass ratio of the solution obtained in step 3), terephthalic acid and tetrabutyl titanate is 49:1:1.
[0017] This ratio facilitates the reaction of the solution obtained in step 3) with terephthalic acid and tetrabutyl titanate.
[0018] As another preferred embodiment, in step 4) of the present invention, 0.8-0.9 g of terephthalic acid is added to the solution obtained in step 3), and stirred for 10-15 minutes at a frequency of 30-50 Hz (preferably 33.33 Hz) using a multi-head magnetic stirrer; after stirring evenly, 0.8-1 mL of tetrabutyl titanate is added dropwise, and the reaction is stirred for 1-3 hours. The magnetic stirrer can be a HJ-4 type magnetic stirrer. The frequency and stirring time of the magnetic stirrer are used to limit the degree of mixing and control the particle size of the catalyst.
[0019] Secondly, in step 5) of the present invention, the ratio of the volume of the solution obtained in step 4) to the volume of the reactor is 1:25.
[0020] This ratio contributes to good pressurization in the hydrothermal reaction and facilitates the synthesis.
[0021] In addition, in step 5 of the present invention, the solution obtained in step 4) is placed in a 90-120 mL reactor and hydroheated at 140-160° C. for 700-730 min; the hydrothermal substance is then washed with ethanol and dried in an oven at 80-90° C. for 10-12 h to obtain a wine red powder substance FeOOH / aMIL-125.
[0022] The invention has beneficial effects.
[0023] The present invention provides a preparation method of a hydrothermally synthesized FeOOH / aMIL-125 composite catalyst. The water purification filler FeOOH / aMIL-125 prepared by the preparation method of the present invention can combine photocatalytic technology with Fenton reaction. The photocatalyst can continuously provide photogenerated electrons to combine with Fe ions in FeOOH, promote the separation of electrons and holes and the circulation of Fe(III) / Fe(II) in the Fenton reaction, and has a self-cleaning function. Therefore, the practical application value of FeOOH / aMIL-125 water purification filler is improved through the photo-Fenton reaction process.
[0024] In the steps 1) to 3) of the present invention, good adsorption performance is established by depositing FeOOH with L-cysteine.
[0025] The present invention composites amorphous MIL-125 and dopes FeOOH through steps 3) to 5), so that FeOOH / aMIL-125 has good photocatalytic and Fenton-like synergistic effects.
[0026] The present invention can control the doping amount of L-FeOOH by changing the addition amount, so as to adjust the size, structure and performance of the catalyst, thereby obtaining a catalyst with better H2O2 addition and pH conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The present invention is further described below in conjunction with the accompanying drawings and specific implementation methods. The protection scope of the present invention is not limited to the following description.
[0028] Figure 1 This is a schematic diagram of the preparation of the FeOOH / aMIL-125-0.3 composite photocatalyst of the present invention.
[0029] Figure 2 This is the SEM spectrum of FeOOH / aMIL-125-0.3 of the present invention.
[0030] Figure 3 The Tafel curves of FeOOH and aMIL-125 under light or no light conditions.
[0031] Figure 4 This is a diagram showing the effect of the FeOOH / aMIL-125-0.3 sample of the present invention degrading TC-HCl.
[0032] Figure 5 This is a diagram showing the degradation of TC-HCl by the FeOOH / aMIL-125-0.1 and FeOOH / aMIL-125-0.6 samples of the present invention.
[0033] Figure 6 Schematic diagram of the energy band structure of FeOOH / aMIL-125-0.3 and FeOOH.
[0034] Figure 7 This is the effect diagram of FeOOH / aMIL-125-0.3 degrading TC-HCl under different pH conditions.
[0035] Figure 8 This is the effect diagram of FeOOH / aMIL-125-0.3 degrading TC-HCl with different H2O2 addition amounts.
[0036] Fig. 9 This is the SEM spectrum of FeOOH / aMIL-125-0.1 of the present invention.
[0037] Fig.10 This is the SEM spectrum of FeOOH / aMIL-125-0.6 of the present invention. DETAILED DESCRIPTION Example
[0038] Step 1) Dissolve 0.59 g of FeCl3·6H2O in 40 mL of deionized water, stir to obtain an orange liquid, and then put it into a 100 mL reactor and heat it at 180°C for 720 min. After the reactor is naturally cooled to room temperature, the obtained product is washed with ethanol and deionized water to obtain a solid product.
[0039] Step 2) The product obtained in step 1) was placed in an oven at 70°C and dried for 10 hours to obtain a dark red powder, namely FeOOH. The obtained 0.3 g of FeOOH and 0.3 g of L-cysteine were dissolved in 35 mL of deionized water, stirred for 24 hours, collected and washed with ethanol. After drying in an oven at 70°C for 10 hours, a wine red powder substance, L-FeOOH, was obtained.
[0040] Step 3) The obtained 0.3 g of L-FeOOH, 36 mL of N,N-dimethylformamide, and 4 mL of methanol were ultrasonicated for 10 minutes to obtain a uniform solution.
[0041] Step 4) Add 0.83 g of terephthalic acid to the solution obtained in step 3), stir evenly, then dropwise add 0.9 mL of tetrabutyl titanate, and stir to react for 2 h.
[0042] Step 5) The solution obtained in step 4) is placed in a 100 mL reactor and hydroheated at 150°C for 720 min; the hydrothermal substance is then washed with ethanol and dried in an oven at 70°C to obtain wine red powder FeOOH / aMIL-125-0.3. The preparation process of FeOOH / aMIL-125-0.3 of the present invention is as follows: Figure 1 shown. Figure 2 It can be seen that the synthesized material exhibits a core-shell structure, with the inner layer of FeOOH as small spheres and the outer layer wrapped with flocculent aMIL-125. Example
[0043] Without adding FeOOH, DMF (36 mL) and methanol (4 mL) were used alone for ultrasonication for 20 min to obtain a uniform solution. Then 0.83 g of terephthalic acid was added to the solution, and 0.9 mL of tetrabutyl titanate was added dropwise after stirring evenly, and the reaction was stirred for 2 h. The resulting solution was placed in a 100 mL reactor and hydrothermal at 150 ° C for 720 min. After washing with ethanol, it was dried in an oven at 70 ° C for 10 h to obtain a white powder, which is aMIL-125.
[0044] Figure 3 The Tafel curves of FeOOH and aMIL-125 under light or no light conditions are shown in Figure 2. Comparing the two conditions of darkness and light, it can be seen that the potential of FeOOH in the dark is lower than that of aMIL-125, indicating that electrons flow from FeOOH to aMIL-125. 2+ Transformed into Fe 3+ And Ti 4+ Transformed into Ti 3+ After adding light, the redox potential of aMIL-125 moved to a more negative direction, while FeOOH moved to a more positive direction under light, indicating that light caused electrons to flow from aMIL-125 to FeOOH. Therefore, after the composite, the Fe required for the Fenton reaction can be obtained by light. 2+ ions and promotes Fe 2+ / Fe 3+ The photo-Fenton catalytic activity was improved by the cyclic process. The current transfer and reversal between FeOOH and aMIL-125 under visible light irradiation indicated that the conduction band electrons of FeOOH combined with the valence band holes of aMIL-125, confirming the existence of Z-type heterojunction.
[0045] Weigh 0.3g FeOOH / aMIL-125-0.3 and add it to 100mL of TC-HCl (20mg / L) aqueous solution (20mg / L means that 1L of TC-HCl aqueous solution contains 20mg of TC-HCl). After stirring in the dark for the first 30min to reach adsorption equilibrium, 50μL of H2O2 was added to the solution under light conditions for degradation test. Under dark conditions without light for the first 30min (i.e., no light conditions), the concentration of TC-HCl in drinking water treated by FeOOH / aMIL-125-0.3 material decreased significantly, showing a strong adsorption effect. And after adding light (light conditions), it showed excellent photo-Fenton performance (such as Figure 4 As shown in Figure 2, further degradation is completed after the addition of light and H2O2). Figure 4 60min( Figure 4 The degradation of TC-HCl was achieved within 60 minutes (60 minutes in the light condition after stirring for 30 minutes in the dark to reach adsorption equilibrium). The dark condition refers to the absence of external natural light, and the light condition refers to the addition of external natural light.
[0046] Figure 4 The ordinate is C0 / C, which is the ratio of the initial concentration of the organic pollutant TC-HCl in the degradation experiment to the concentration after the reaction, indicating the degradation efficiency of the catalyst of the present invention. Example
[0047] The amount of L-FeOOH in step 3) of Example 1 was reduced to 0.1 g or increased to 0.6 g, respectively, and then mixed with DMF (36 mL) and methanol (4 mL) and repeated the above experiment to obtain two control materials, FeOOH / aMIL-125-0.1 or FeOOH / aMIL-125-0.6. Weigh 20 mg (Example 2 is the synthesis process, weigh 0.3 g FeOOH / aMIL-125-0.3. Example 3 is an experiment for photo-Fenton reaction performance test, weigh 20 mg of FeOOH / aMIL-125-0.1 or FeOOH / aMIL-125-0.6) of FeOOH / aMIL-125-0.1 or FeOOH / aMIL-125-0.6, and add it to 100 mL of TC-HCl (20 mg / L) solution. After stirring for 30 min in the dark to reach adsorption equilibrium, add 50 μL of H2O2 to the solution under light conditions for degradation test.
[0048] like Figure 5It can be seen that FeOOH / aMIL-125-0.1 and FeOOH / aMIL-125-0.6 also showed adsorption degradation in the first 30 minutes and degradation in the last 60 minutes (the whole reaction was an adsorption equilibrium reaction under dark conditions without light in the first 30 minutes, and a photo-Fenton reaction of the test catalyst on TC-HCl under light and H2O2 addition after 30 minutes of reaction) under the synergistic effect of the photo-Fenton reaction. The degradation efficiencies of the two were 63% and 82%, respectively, which were lower than those of FeOOH / aMIL-125-0.3, indicating that FeOOH / aMIL-125-0.3 had the highest adsorption and photo-Fenton degradation efficiency for the organic pollutant TC-HCl in water and the best catalytic activity.
[0049] contrast Figure 6 It can be seen that the band gap of FeOOH / aMIL-125-0.3 is significantly reduced compared with FeOOH. This indicates that the photogenerated electron-hole recombination efficiency of FeOOH / aMIL-125-0.3 is low, indicating that the composite of aMIL-125 and FeOOH is not only an important active site for the photo-Fenton reaction, but also effectively inhibits the rapid electron-hole recombination of the catalyst and improves the photocatalytic performance. Example
[0050] The samples of Example 1 were subjected to TC-HCl degradation experiments at different pH values and different H2O2 addition amounts. Figure 7 As shown in the figure, the degradation efficiency of the sample increases first and then decreases in the pH range of 3 to 11, indicating that the FeOOH / aMIL-125-0.3 of the present invention has the best performance when it is neutral (i.e., pH value is 7). Figure 8 As shown, when the amount of H2O2 added increased from 30 μL to 100 μL, the degradation rate changed from high to low, and the performance was best at 50 μL, indicating that FeOOH / aMIL-125-0.3 has a good pH application range and a lower H2O2 dosage, so the present invention has better practical application value.
[0051] Comparative Example 1 In step 3) of Example 1, 0.3 g of L-FeOOH was replaced with 0.1 g of L-FeOOH or 0.6 g of L-FeOOH, and other steps and material usage remained unchanged to obtain FeOOH / aMIL-125-0.1 or FeOOH / aMIL-125-0.6.
[0052] The morphology of the material changed significantly after changing the amount of L-FeOOH added, such as Fig. 9 As shown in the figure, the shape of the FeOOH / aMIL-125-0.1 pellet is more obvious and the particles attached to the pellet are relatively sparse. Fig.10As shown, FeOOH / aMIL-125-0.6 has more pellets attached, and even forms a network connection between each pellet. The change in the ratio of pellets to flocs corresponds to the change in the ratio of FeOOH to aMIL-125. When the ratio is 1:1 and 1:5, the degradation performance is not as good as the adsorption and photo-Fenton performance of FeOOH / aMIL-125-0.3 in the present invention.
[0053] It can be understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.
Claims
1. A method for preparing a water purification filler with adsorption and photo-Fenton properties, characterized in that The following steps are involved: Step 1) dissolving FeCl3·6H2O in deionized water, stirring to obtain a uniform orange solution, and then placing the solution in a reactor for hydrothermal treatment; after the reactor is naturally cooled to room temperature, washing the obtained product with ethanol and deionized water to obtain a solid product; Step 2) The product obtained in step 1) is placed in an oven and dried to obtain a dark red powder substance FeOOH; the obtained FeOOH and L-cysteine are dissolved in deionized water, stirred, collected and washed with ethanol; after drying in an oven, a wine red powder substance L-FeOOH is obtained; Step 3) mixing the obtained L-FeOOH with N,N-dimethylformamide and methanol by ultrasonication to obtain a uniform solution; Step 4) adding terephthalic acid to the solution obtained in step 3), stirring evenly and then adding tetrabutyl titanate dropwise; Step 5) The solution obtained in step 4) is placed in a reaction kettle and hydroheated; the solid matter after hydroheating is then washed with ethanol and dried in an oven to finally obtain a wine red powder substance FeOOH / aMIL-125-0.
3.
2. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 1), the mass ratio of FeCl3·6H2O to deionized water is 3:
200.
3. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that The step 1) dissolves 0.5-0.6 g of FeCl3·6H2O in 30-50 mL of deionized water, stirs for 10-15 minutes using a multi-head magnetic stirrer at a frequency of 30-35 Hz to obtain a uniform orange solution, and then puts the solution into a 90-120 mL reactor and hydroheats at 150-200° C. for 700-750 minutes; after the reactor is naturally cooled to room temperature, the obtained product is centrifuged and washed with ethanol and deionized water at a speed of 8000-9000 rpm for 3-5 minutes to obtain a solid product.
4. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 2), the mass ratio of FeOOH, L-cysteine and deionized water is 1:1:
12.
5. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 2), the product obtained in the step 1) is placed in an oven at 60-80° C. and dried for 9-12 hours to obtain a dark red powder substance FeOOH; 0.3-0.5 g of FeOOH and 0.3-0.5 g of L-cysteine are dissolved in 30-40 mL of deionized water, stirred for 20-30 hours, collected and washed with ethanol; and dried in an oven at 60-80° C. for 9-12 hours to obtain a wine red powder substance L-FeOOH.
6. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 3), the mass ratio of L-FeOOH, N,N-dimethylformamide and methanol is 1:120:
14.
7. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 3), 0.1 to 0.6 g of the obtained L-FeOOH is mixed with 35 to 40 mL of N,N-dimethylformamide and 3 to 5 mL of methanol by using an ultrasonic cleaner at a frequency of 80 to 100 Hz for 10 to 15 minutes to obtain a uniform solution.
8. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 4), the mass ratio of the solution obtained in step 3), terephthalic acid and tetrabutyl titanate is 49:1:
1.
9. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 4), 0.8-0.9 g of terephthalic acid is added to the solution obtained in the step 3), and the mixture is stirred for 10-15 minutes at a frequency of 30-50 Hz using a multi-head magnetic stirrer; after stirring evenly, 0.8-1 mL of tetrabutyl titanate is added dropwise, and the mixture is stirred for reaction for 1-3 hours.
10. A method for preparing a water purification filler having adsorption and photo-Fenton properties according to claim 1, characterized in that In the step 5), the solution obtained in the step 4) is placed in a 90-120 mL reactor and hydroheated at 140-160° C. for 700-730 min; the hydrothermal substance is then washed with ethanol and dried in an oven at 80-90° C. for 10-12 h to obtain a wine red powder substance FeOOH / aMIL-125.
Citation Information
Patent Citations
Photo-Fenton catalyst and preparation method and application thereof
CN110302839A
Photo-Fenton catalyst as well as preparation method and application thereof
CN115212899A
Metal organic framework compound as well as preparation method and application thereof
CN119184112A
Preparation method and application of adsorption-photocatalysis bifunctional MILs material
CN119259011A
catalyst for hydrogen chloride oxdidation reaction process including inorganic additive and method for manufacturing the same
KR1020220109106A